Eastern Europe since 1945 - Swain, Geoffrey 1950-; Swain, Nigel (Palgrave Macmillan, 2009)
"This essential text has been fully revised, updated and expanded to take account of new material and events since the publication of the third edition. The last chapters focus on the inclusion of most of the Eastern European states into the EU and the book now also features more tables, maps and Further Reading"--Provided by publisher.
Keywords: Geschichte 1945-1989; Geschichte 1945-; Geschichte; Kommunismus; Politik; Communism -- Europe, Eastern -- History; Alltag; Europe, Eastern -- Politics and government -- 1945-1989; Osteuropa; Ostblock